Characterization of Plasmodium falciparum macrophage migration inhibitory factor homologue and its cysteine deficient mutants. (April 2022) - Schipper, Susanne; Springer, Eric; Hahn, Julia; Rahlfs, Stefan; Bourilhon, Priscila; Bernhagen, Jürgen; Becker, Katja; Przyborski, Jude M.
Abstract: Plasmodium falciparum macrophage migration inhibitory factor (PfMIF) is a homologue of the multifunctional human host cytokine MIF (HsMIF). Upon schizont rupture it is released into the human blood stream where it acts as a virulence factor, modulating the host immune system. Whereas for HsMIF a tautomerase, an oxidoreductase, and a nuclease activity have been identified, the latter has not yet been studied for PfMIF. Furthermore, previous studies identified PfMIF as a target for several redox post-translational modifications. Therefore, we analysed the impact of S -glutathionylation and S -nitrosation on the protein' s functions. To determine the impact of the four cysteines of PfMIF we produced His-tagged cysteine to alanine mutants of PfMIF via site-directed mutagenesis. Recombinant proteins were analysed via mass spectrometry, and enzymatic assays. Here we show for the first time that PfMIF acts as a DNase of human genomic DNA and that this activity is greater than that shown by HsMIF. Moreover, we observed a significant decrease in the maximum velocity of the DCME tautomerase activity of PfMIF upon alanine replacement of Cys3, and Cys3/Cys4 double mutant. Lastly, using a yeast reporter system, we were able to verify binding of PfMIF to the human chemokine receptors CXCR4, and demonstrate a so-far overlooked binding to CXCR2, both of which function as non-cognate receptors for HsMIF. While S-glutathionylation and S-nitrosation of PfMIF did not impair the tautomerase activity of PfMIF, activation of these receptors was significantly decreased. Graphical abstract: Unlabelled Image Highlights: P. falciparum macrophage migration inhibitory factor (PfMIF) shows DNase activity. Mutation of cysteine residues in PfMIF significantly impairs the protein' s tautomerase activity. PfMIF activates not only CXCR4, but also CXCR2 human receptors. Redox modifications of PfMIF significantly decrease receptor activation.